HEAVY METALS ANALYSIS OF MAI-ALLO POND IN GWALE LOCAL GOVERNMENT AREA, KANO STATE, NIGERIA - Karaye, M. M.; Ibrahim, H. A. (FUDMA Journal of Sciences, 2020)
Study of Seven heavy metals namely, Zinc, Lead, Copper, Cadmium, Manganese, Chromium and Nickel was conducted in Mai-Allo pond, Gwale, Kano State in order to assess the concentration of the heavy metals in the pond. The results of the heavy metals showed that Zn has a value of 0.34±0.17 mg-l in the wet season and 0.49±0.37 mg-l in the dry season, Cu has a value of 1.42±0.14 mg-l in the wet season and 0.64±0.09 mg-l in the dry season, and Ni also has 0.12±0.02 mg-l in the wet season and 0.23±0.13 mg-l in the dry season, all these were within acceptable limits, while Pb with a value of 0.05±0.02 mg-l was within the limits during the wet season but during the dry season, the value 0.14±0.09mg-l exceeds the limits. Cd has a value of 0.06±0.01 in the wet season and 0.17±0.12 in the dry season, Cr has 0.36±0.12 in the wet season and 0.04±0.07 in the dry season, and Mn also has values of 0.46±0.12 and 0.22±0.03 in the wet and dry seasons respectively. Hence there was no significant difference (P>0.05) in the mean values of the sampling stations of the heavy metals during the wet and dry seasons. The study showed that the pond water was polluted with some heavy metals and hence measures must be taken to ensure the safety of the aquatic ecosystem, humans and the environment.